Legal Review of Medical Crime: Patient Protection and Professional Responsibility in Medical Practice - Thahir, Putri Shafarina; Tongat, Tongat (Universitas Muhammadiyah Malang, 2024)
This article discusses a review of the law related to medical crimes in the context of patient protection and professional responsibility in medical practice in Indonesia. Employing a normative juridical research method, this study combines conceptual analysis with statutory regulation, and there are two main topics studied, namely: (1) What patient rights are protected by law in medical practice in Indonesia and (2) The role of the code of ethics in determining professional responsibilities for practitioners and its relationship to medical criminal law. The first discussion elaborates on patients' fundamental rights protected by various laws and regulations in Indonesia, including the right to information, freedom to consent or refuse medical treatment, confidentiality of information, security and safety, comfort, and compensation. The most important and fundamental legal rules in the health legal system in Indonesia are Law Number 29 of 2004 concerning Medical Practice, Law Number 36 of 2009 concerning Health, Law Number 44 of 2009 concerning Hospitals, Law Number 17 of 2023 concerning Health, and Criminal Code / Kitab Undang-Undang Hukum Pidana (KUHP). The following section explains the crucial role of medical ethics codes in determining the professional responsibilities of medical practitioners, highlighting their intersection with criminal law. For instance, the principle of non-maleficence (not harm) can be linked to criminal negligence if a healthcare professional's actions cause significant patient injury. Similarly, the principle of respect for patient autonomy aligns with the legal requirement for informed consent. By exploring these connections with real-life examples, the article aims to comprehensively understand how law and ethics work together to protect patient rights in Indonesia. The relationship between the code of ethics and medical criminal law is discussed, emphasizing the consequences of ethical violations that can result in criminal sanctions. By analyzing these aspects, this article examines how medical criminal law can achieve justice for patients harmed by rights violations and ensure that the professional responsibilities of medical personnel are fulfilled. Hopefully, this study will improve the quality of health services and more transparent and accountable medical practices in Indonesia.